The Relationship between Academic Crafting, Work-School Facilitation and Academic Engagement: A Mediated Model - Kerse, Gökhan; Çil, Umut (Makara Human Behavior Studies in Asia, 2024)
This research examines the relationship between academic crafting, work-school facilitation and academic engagement in higher education. Based on the Job Demands-Resources (JD-R) Model, the research sought to determine how students' alignment of academic activities with personal preferences and interests (academic crafting) affects academic engagement and whether work-school facilitation mediates this effect. The research therefore emphasized the delicate balance that students strike between their work obligations and their scholarly activities. Our research hypotheses focused on understanding how academic crafting directly and indirectly affects student engagement. The research data were obtained from a sample of students enrolled in postgraduate programs and actively working in the labor market. The sample included a higher proportion of male (108), married people (88), those aged 26 to 35 (89), students pursuing a master's degree with a thesis (112), and those who had been employed for 6–10 years (47). The analyses revealed that academic crafting has a direct positive effect on academic engagement. Moreover, in the research, academic crafting not only directly affected academic engagement, but also indirectly through work-school facilitation. In this case, it was determined that work-school facilitation had a mediating role in the study. Therefore, students who proactively aligned their course-related activities with their interests effectively balanced their work demands and academic responsibilities and exhibited more dedication and enthusiasm in their academic studies.